Roles of MEM1 in safeguarding Arabidopsis genome against DNA damage, inhibiting ATM/SOG1‐mediated DNA damage response, and antagonizing global DNA hypermethylation. Issue 1 (21st January 2022) - Wang, Qianqian; La, Yumei; Xia, Huihui; Zhou, Shaoxia; Zhai, Zhaoyu; La, Honggui
Abstract: Arabidopsis methylation elevated mutant 1 ( mem1 ) mutants have elevated levels of global DNA methylation. In this study, such mutant alleles showed increased sensitivity to methyl methanesulfonate (MMS). In mem1 mutants, an assortment of genes engaged in DNA damage response (DDR), especially DNA‐repair‐associated genes, were largely upregulated without MMS treatment, suggestive of activation of the DDR pathway in them. Following MMS treatment, expression levels of multiple DNA‐repair‐associated genes in mem1 mutants were generally lower than in Col‐0 plants, which accounted for the MMS‐sensitive phenotype of the mem1 mutants. A group of DNA methylation pathway genes were upregulated in mem1 mutants under non‐MMS‐treated conditions, causing elevated global DNA methylation, especially in RNA‐directed DNA methylation (RdDM)‐targeted regions. Moreover, MEM1 seemed to help ATAXIA‐TELANGIECTASIA MUTATED (ATM) and/or SUPPRESSOR OF GAMMA RESPONSE 1 (SOG1) to fully activate/suppress transcription of a subset of genes regulated simultaneously by MEM1 and ATM and/or SOG1, because expression of such genes decreased/increased consistently in mem1 and atm and/or sog1 mutants, but the decreases/increases in the mem1 mutants were not as dramatic as in the atm and/or sog1 mutants. Thus, our studies reveals roles of MEM1 in safeguarding genome, and interrelationships among DNA damage, activation of DDR, DNA methylation/demethylation, and DNA repair. Abstract : Mutations of MEM1 causes increased DNA methylation levels genome‐wide. mem1 mutants exhibited enhanced MMS sensitivity, which stemmed from elevated DNA damage and activated DDR. Thus, MEM1 appears to play important roles in preventing DNA lesions and maintaining normal expression of genes involved in DNA repair.